(untitled) (Agroindustria, Sociedad y Ambiente, 2016)
The purpose of this article is show the design of future indicators of the Environment variable for Morán Municipality, Lara state of Venezuela, in a timeframe of 10 years (2010-2020); The study begins with the determination of current territory conditions and the development perspectives. It is field research with a qualitative and quantitative approach, by the fact that a prospective study and because mathematical techniques and procedures apply. First are placed the theoretical foundations that sensitize the researcher, such as prospective methodology and Delphi technique. Subsequently, the current situation of the locality is described, with the intention of determining the social profile and subsequently described the current situation of the town with the intention of meeting the social profile of the same and then designing scenarios of the Environment variable for the Municipality Moran. The variable was dimensioned in four categories: Status of water resources, soil, flora and fauna; Natural Disaster Prevention, Industrial Urban Population Growth and Demand of variable Environment for higher education institutions. The results show an increasing trend in the four dimensions analyzed, with a slight tendency to stay the same, in dimension: Population Growth, Urban. Although experts note an increase in the dimensions studied and the Environmental variable has great potential that could strengthen to reduce the threats and weaknesses, it is concluded that the studied does not contribute enough to the local development of the municipality in the time period specified.